2020
DOI: 10.1021/acsami.0c12199
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent, Flexible, and Self-Healable Thermoacoustic Loudspeakers

Abstract: Thermoacoustic (TA) loudspeakers have garnered significant attention in recent times as a novel film speaker that utilizes temperature oscillation to vibrate the surrounding air. Conventional film-type TA loudspeakers are known to experience problems when external environments damage their conductive networks, causing them to malfunction. Therefore, introducing self-healing polymers in TA loudspeakers could be an effective way to restore the surface damage of conductive networks. In this study, we present tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…[31][32][33] Beneting from the dynamic nature, HUBs, formed by a condensation reaction between the isocyanate and hindered amine, have been widely used to fabricate polyurea or poly(urea-urethane), which are capable of healing, recycling, and shapememory via a dissociative exchange mechanism. [34][35][36][37] Herein, we report a straightforward, catalyst-free, fast and efficient preparation method of colorless and transparent PMMA CANs using only easily available chemicals via HUB crosslinking strategies. It was found that the Young's modulus, tensile strength, and toughness simultaneously increased from 973 MPa, 46.2 MPa, 0.85 MJ m À3 to 1396 MPa, 76.5 MPa, and 13.4 MJ m À3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Beneting from the dynamic nature, HUBs, formed by a condensation reaction between the isocyanate and hindered amine, have been widely used to fabricate polyurea or poly(urea-urethane), which are capable of healing, recycling, and shapememory via a dissociative exchange mechanism. [34][35][36][37] Herein, we report a straightforward, catalyst-free, fast and efficient preparation method of colorless and transparent PMMA CANs using only easily available chemicals via HUB crosslinking strategies. It was found that the Young's modulus, tensile strength, and toughness simultaneously increased from 973 MPa, 46.2 MPa, 0.85 MJ m À3 to 1396 MPa, 76.5 MPa, and 13.4 MJ m À3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in SHMs in the area of organic electronic materials have been well demonstrated and have garnered intensive attention. Self-healable organic electronic materials have been used in devices such as energy-harvesting devices, field-effect transistors, sensors, and electronic skin [ 11 , 12 , 13 , 14 , 15 , 16 ]. Over the past few years, important advances in techniques for constructing organic electronics with high performance and high safety have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, self-healing protective coatings have attracted intensive attention from both academia and industry as a potent technology to extend the service life of high-priced products whose aesthetics need to also be maintained, such as automobiles and electronic products. Unlike the conventional scratch removal process that requires polishing the entire coating, self-healing protective coatings provide a more economical repair method by healing the scratched surface repeatedly without loss of the coating materials. Because most protective coatings used in these applications require optical transparency and high durability, intrinsic self-healing mechanisms offer advantages over extrinsic self-healing mechanisms, which tend to cause haze by interfacial light scattering between microcapsules and the coating materials. However, achieving high self-healing performance in intrinsic self-healing coatings while maintaining good mechanical and chemical durability is more difficult than with other forms of polymer network materials, such as elastomers, adhesives, and gels. This difference is attributed to the self-healing process requiring elastic recovery and/or physical flow around a wound area, followed by chemical bonding at the molecular level.…”
Section: Introductionmentioning
confidence: 99%